Tough fiber-reinforced composite ionogels with crack resistance surpassing metals - Xiaolin Lyu; Kun Yu; Haoqi Zhang; Piaopiao Zhou; Zhihao Shen; Zhigang Zou (Nature Communications)
Abstract Ion-conductive materials have received much attention because of their good mechanical and electrical properties. However, their practical applications are still hampered by limited toughness and crack resistance, stemming from the restricted size of energy dissipation zones, which impacts their reliability and durability. Herein, tough fiber-reinforced composite ionogels (FRCIs) with crack resistance are fabricated by incorporating high-performance fibers into elastic ionogels to efficiently dissipate energy. The FRCIs exhibit good tearing toughness, high strength, high elastic modulus, and low bending modulus. The toughness and crack resistance of the FRCI far exceed that of previously reported gel materials, even outperforming metals and alloys. Furthermore, the electrical resistance of FRCI shows high sensitivity to deformation. Moreover, it remains undamaged after undergoing 10,000 bending cycles when fixing the artificial bone, and possesses self-sensing impact resistance, demonstrating great potential in intelligent robots and smart protective equipment.